Lecturers’ organizational citizenship behaviours during COVID-19 pandemic / Shaiful Annuar Khalid … [et al.] - Khalid, Shaiful Annuar; Abdul Rahman, Norshimah; Darus, Norizul Azida; Shahruddin, Shafiq (Universiti Teknologi MARA, 2021)
A limited number of studies indicate that organizational citizenship behavior (OCB) have the potential to contribute to organizational and individual performance. Educators who have positive behaviors such as helping behavior can help facilitate the learning process. With the spread of COVID-19 pandemic which has led to the growth of online learning, OCBs among educators is needed in facilitating students’ learning process. This study was conducted to examine the practice of OCB among lecturers from an institution of higher learning who are currently using online learning as the platform of teaching. Based on the input obtained from 136 students, the results found that lecturers are indeed showing high levels of OCB. These students have reported a total of forty behaviors classified as OCB among lecturers. In terms of implications, lecturers’ OCB are seen to be able to support the online learning process which is a new method for most students.